Animação espacial e o movimento das imagens na tecnocultura contemporânea - Bozzetti, Augusto Ramos (Universidade do Vale do Rio dos Sinos, 2024)
This research is based on an epistemological proposal that perceives the concept of animation as fundamental to the study of the audiovisual matter, with the aim of developing a perspective capable of recognizing it in media objects that are not traditionally thought of as animated. Under an anachronistic look provided by the lens of the audiovisualities of technoculture, we investigate the peculiar way in which animation manifests itself, having in the spatial organization of its modularity a vertex as important as the temporality of the images that move. Through excavatory movements that aim to produce collections of images from different periods, we seek to investigate, therefore, spatial animation as a technical/aesthetic becoming and its updating movements, especially in contemporary media. In this way, we seek to understand how spatial animation is helping to precipitate not only new media objects, but also new media environments that, in turn, produce new kinds of users, new softwarized interfaces and new ways of displaying and transmit moving images, reorganizing man's sensitive experience of the world through an audiovisualized process that, therefore, has animation in a central and decisive position.
Keywords: Animação espacial; Animação; Audiovisualidades; Tecnocultura; Spatial animation; Animation; Audiovisualities; Technoculture; ACCNPQ::Ciências Sociais Aplicadas::Comunicação